Shifts in policy and practice in early childhood curriculum priorities in Aotearoa-New Zealand: Entanglements of possibility and risk. Issue 6 (September 2020) - Haggerty, Maggie; Loveridge, Judith; Alcock, Sophie
Abstract: Recent policy developments in the early childhood (EC) care and education sector in Aotearoa-New Zealand have seen a shift in focus from children and play to learners and learning. While few would argue against learning as priority this article raises pressing questions about the 'intended' and '(un)intended' consequences of this turn. We analyse national education policy reforms that have served to promote the construction of child-as-learner-subject, alongside moves internationally toward the learnerfication of EC services (Biesta, 2010). As a particular focus, we examine the legacy EC curriculum policy has drawn on from indigenous Māori discourses, as a complex entanglement of both possibility and risk. We focus also on how, in this policy context, an intermix of 'old' and 'new' curriculum priorities was playing out in one EC setting and how teachers sought to navigate the complex entanglement this effected in practice. On the basis of our analyses, we argue that the problem is not with learning as priority, but with the (school-referenced) narrowing of curriculum, the prioritising of homogenised predetermined outcomes and the ways in which children (parents and teachers) are being positioned in these particular constructions of learners and learning.